Pro RESTful APIs : design, build and integrate with REST, JSON, XML and JAX-RS - Patni, Sanjay (Apress, 2017)
Discover the RESTful technologies, including REST, JSON, XML, JAX-RS web services, SOAP and more, for building today's microservices, big data applications, and web service applications. This book is based on a course the Oracle-based author is teaching for UC Santa Cruz Silicon Valley which covers architecture, design best practices and coding labs. Pro RESTful APIs: Design gives you all the fundamentals from the top down: from the top (architecture) through the middle (design) to the bottom (coding). This book is a must have for any microservices or web services developer building applications and services. You will: Discover the key RESTful APIs, including REST, JSON, XML, JAX-RS, SOAP and more Use these for web services and data exchange, especially in today's big data context Harness XML, JSON, REST, and JAX-RS in examples and case studies <apply best="" practices="" to="" your="" solutions’="" architecture .